Increased Incidence of Late-Onset Circulatory Collapse after Changing Clinical Practice: A Retrospective Investigation of Causative Factors - Shimokaze, Tomoyuki; Saito, Emi; Akaba, Kazuhiro (American Journal of Perinatology, 2015)
Objective Acute primary profound circulatory failure responsive to glucocorticoid therapy after the first week of age in preterm infants is termed late-onset circulatory collapse (LCC). This study was performed to identify factors that notably increased the incidence of LCC after various management practices were changed.Study Design We retrospectively studied the clinical characteristics of infants (<29 weeks' gestation) before (n = 26) and after (n = 35) implementing the following practice changes: stress reduction, conservative replacement of thyroid hormone, positive antenatal glucocorticoid administration, sedation with fentanyl (<7 days after birth), and hydrocortisone therapy for hypotension.Results After the aforementioned changes, the incidence of LCC increased from 4 to 43%, and that of intraventricular hemorrhage decreased from 42 to 9%. Antenatal glucocorticoids (75 vs. 20%), fentanyl (94 vs. 53%), and hydrocortisone (63 vs. 31%) (<2 weeks of age) were given to infants with LCC and non-LCC. After the practice changes, infants with LCC had lower serum sodium levels than did infants without LCC at 7 to 14 days of age.Conclusion Relative hyponatremia was an early sign of imminent LCC. In addition to adrenal prematurity, the antenatal administration of glucocorticoids and fentanyl, which influence adrenal function, might increase the incidence of LCC.
Keywords: adrenal insufficiency; fentanyl; glucocorticoid; hyponatremia; opioid